2021
DOI: 10.1108/srj-10-2020-0398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the awareness of brand-related CSR activities on purchase intention for luxury brands

Abstract: Purpose The purpose of this study is to investigate the impact of luxury buyers' awareness of a luxury brand's corporate social responsibility (CSR) activities together with its individual brand-related sustainable dimensions (in terms of economic, societal and environmental) and luxury values on purchase intention for luxury products and, as a result, highlight the potential implications of these relationships for the luxury industry. Design/methodology/approach A luxury purchase intention model, which assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
1
12
1
Order By: Relevance
“…Prior studies by Pomering and Dolnicar (2009), Palihawadana et al (2016), Cerkasov et al (2017) and Collins and Kug (2021) found that CA is a determinant of consumers' future behaviour. Besides, the results of some recent studies indicated that CA and CB are influenced positively when consumers are aware of the businesses and their initiatives (Olšanov a et al, 2022;Stadlthanner et al, 2022). For instance, there is evidence that consumers who are concerned about environmental issues are more likely to buy green products (do Paço et al, 2019).…”
Section: Impact Of Consumer Attitude On Consumer Purchasing Behaviourmentioning
confidence: 99%
“…Prior studies by Pomering and Dolnicar (2009), Palihawadana et al (2016), Cerkasov et al (2017) and Collins and Kug (2021) found that CA is a determinant of consumers' future behaviour. Besides, the results of some recent studies indicated that CA and CB are influenced positively when consumers are aware of the businesses and their initiatives (Olšanov a et al, 2022;Stadlthanner et al, 2022). For instance, there is evidence that consumers who are concerned about environmental issues are more likely to buy green products (do Paço et al, 2019).…”
Section: Impact Of Consumer Attitude On Consumer Purchasing Behaviourmentioning
confidence: 99%
“…Brands with a negative brand AGR are losing their market position and thus their sustainability (Olšanová, Escobar Ríos, Cook, Král, & Zlatić, 2021). This is the type of metric that brand managers will need in the future to properly plan for and allocate finite corporate resources (Halwani, 2020).…”
Section: Brand Sustainabilitymentioning
confidence: 99%
“…The recent understanding of CSR addresses such questions as exactly who or what are companies responsible for and what is their aim when implementing CSR practices. The work of Olšanová et al (2022) defined how much pressure businesses receive to adapt CSR and sustainable development principles from customers and to what degree this affects their competitive advantage (Olšanová et al, 2022). CSR activities have a positive link with customer loyalty, financial performance, and future growth possibilities (Podgorodnichenko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%